2023
DOI: 10.3389/fnagi.2023.1051177
|View full text |Cite
|
Sign up to set email alerts
|

Study of gray matter atrophy pattern with subcortical ischemic vascular disease-vascular cognitive impairment no dementia based on structural magnetic resonance imaging

Abstract: ObjectiveThis study explored the structural imaging changes in patients with subcortical ischemic vascular disease (SIVD)-vascular cognitive impairment no dementia (VCIND) and the correlation between the changes in gray matter volume and the field of cognitive impairment to provide new targets for early diagnosis and treatment.MethodsOur study included 15 patients with SIVD-normal cognitive impairment (SIVD-NCI), 63 with SIVD-VCIND, 26 with SIVD-vascular dementia (SIVD-VD), and 14 normal controls (NC). T1-weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 26 publications
1
7
0
1
Order By: Relevance
“…Such alterations may play a crucial role in the development and manifestation of subcortical VCI. The findings of this study provide valuable evidence that helps in explaining the underlying mechanisms of subcortical VCI ( 16 ). It highlights the importance of identifying and understanding the structural changes occurring in the brain, which can contribute to better diagnosis, management, and treatment strategies for patients with subcortical VCI.…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…Such alterations may play a crucial role in the development and manifestation of subcortical VCI. The findings of this study provide valuable evidence that helps in explaining the underlying mechanisms of subcortical VCI ( 16 ). It highlights the importance of identifying and understanding the structural changes occurring in the brain, which can contribute to better diagnosis, management, and treatment strategies for patients with subcortical VCI.…”
Section: Introductionmentioning
confidence: 83%
“…In their study, Tan and colleagues aimed to investigate the structural imaging changes occurring in patients with SIVD-VCIND and SIVD-VaD, which are subtypes of SIVD ( 16 ). They found that gray matter atrophy was observed in multiple brain regions in both groups.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The temporal lobe plays a crucial role in the normal memory function and the processing of auditory information ( Tan et al, 2023 ). Our study observed significant associations between the atrophy of left middle temporal gyrus and the decreased auditory memory scores in SIVD-CI group.…”
Section: Discussionmentioning
confidence: 99%
“…의 수행력이 DAT와 유사하고 (Freitas et al, 2018;Villardita, 1993), vMCI의 경우 MCI-nov보다 수행력이 저하되는 것으로 나타나거나 (Nordlund et al, 2007) 수행력에 유의미한 차이가 없다는 연구도 함께 보고되었다 (Nyström et al, 2015). Reiter, 2000;Kaul et al, 2022;Lee et al, 2017;Lukatela et al, 1998;Park et al, 2006;Paul et al, 2001a;Tan et al, 2023;Traykov et al, 2005;Villardita, 1993;Vuorinen et al, 2000) DAT와 비교하여 수행력이 높다는 결과가 많았다 (Braaten et al, 2006;Freitas et al, 2018;Golden et al, 2005;Knopman et al, 2011;Lukatela et al, 1998;Morris et al, 2016;Oh et al, 2010;Vuorinen et al, 2000). 이와 반대로 DAT보다 대면이름대기 수행력이 저하된다는 보고 (Er et al, 2017;Jang & Kim, 2012;Lee et al, 2017)와 유의미한 차 이가 나타나지 않았다는 보고도 일부에서 확인되었다 (Baillon et al, 2003;Bentham et al, 1997;Lafosse et al, 1997;Laine et al, 1997;Park et al, 2006;Villardita, 1993).…”
Section: 토큰 검사의 수행력을 환자군 간 비교하여 살펴보았을 때 Vadunclassified